2023
DOI: 10.3390/mi14112107
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Parametric Analysis of the Separation of Ultra-Small, Aqueous Superparamagnetic Iron Oxide Nanoparticle Suspensions under Quadrupole Magnetic Fields

Stefano Ciannella,
Xian Wu,
Cristina González-Fernández
et al.

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) have gathered tremendous scientific interest, especially in the biomedical field, for multiple applications, including bioseparation, drug delivery, etc. Nevertheless, their manipulation and separation with magnetic fields are challenging due to their small size. We recently reported the coupling of cooperative magnetophoresis and sedimentation using quadrupole magnets as a promising strategy to successfully promote SPION recovery from media. However, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This reduction in interparticle distance causes an augment in magnetic dipole-dipole interactions, leading to potential particle aggregation when highly concentrated SPION solutions are used. Indeed, it has been recently shown that, through batch separation experiments of 20 nm and 30 nm SPIONs at various initial concentration values of the particle dispersion, higher initial concentrations of SPIONs enhanced the magnetophoretic separation time [63]. However, for an optimal operation of this principle, one must consider the economic viability of the process, since highly concentrated solutions can be detrimental to the process economy and become environmentally non-friendly.…”
Section: Low-gradient Magnetic Separation (Lgms)mentioning
confidence: 99%
“…This reduction in interparticle distance causes an augment in magnetic dipole-dipole interactions, leading to potential particle aggregation when highly concentrated SPION solutions are used. Indeed, it has been recently shown that, through batch separation experiments of 20 nm and 30 nm SPIONs at various initial concentration values of the particle dispersion, higher initial concentrations of SPIONs enhanced the magnetophoretic separation time [63]. However, for an optimal operation of this principle, one must consider the economic viability of the process, since highly concentrated solutions can be detrimental to the process economy and become environmentally non-friendly.…”
Section: Low-gradient Magnetic Separation (Lgms)mentioning
confidence: 99%